ANALISIS PEMASARAN GETAH DAMAR MATA KUCING (Shorea javanica) DI KABUPATEN LAMPUNG BARAT - Afriani, Ismalia (Lampung University)
The resin commodity to the market is quiet complicated.Â Large number of labour within a long line of marketing trace, creates the inefficient marketing system. The research aims to analyse the market structure and to determine the efficiency of resin marketing system. The study employs descriptive analysis as well as statistics to determine ratio profit margin and market integration. The field study was conducted from November to December, 2006 in Subdistricts of Pahmungan, Penengahan, and Negeri Ratu Ngaras, West Lampung. The study suggests that there are three channels of resin marketing.Â One channel offers the highest share for the farmer, and has simple marketing line, i.e. from farmers to mid size collectors and then to big traders. On the other hand, operational efficiency and price transmission explain that the marketing of resin is inefficient due to the market structure is oligopoly market.Â Resin market is unique as it is solely produced by farmers from this region and is known globally for its contribution to the natural conservation of damar forest.